ORIGIN OF SIO2-RICH COMPONENTS IN ORDINARY CHONDRITES - Hezel D.C.; Palme H.; Nasdala L.; Brenker F.E. (My University, 2006)
Silica-rich objects are common minor components in ordinary chondrites (OC), occurring as fragments and as chondrules. Their typical paragenesis is orthopyroxene + SiO2 (with bulk SiO2 >65 wt%) and occasionally with additional olivine and/or spinel. Individual silica-rich components (SRC) have previously been studied in various types of OCs, although there is only one comprehensive study of these objects by Brigham et al. [Brigham, C.A., Murrell, M.T., Yabuki, H., Ouyang, Z., El Goresy, A., 1986. Silica-bearing chondrules and clasts in ordinary chondrites. Geochim. Cosmochim. Acta 50, 1655-1666]. Several different explanations of how SRCs formed have been published. The main question is how silica-enrichment was achieved, because CI-chondritic atomic Mg/Si-ratio is 1.07 and as a consequence only olivine and pyroxene, but no free silica should be stable. There are two basic possibilities for the SiO2-enrichment: (1) a RedOx-mechanism or magmatic fractionation on the parent body and (2) fractional condensation or recycling of chondrule mesostasis in the solar nebula. To better constrain the origin of these objects, we measured major and rare earth elements in SRCs of various types of ordinary chondrites, and in addition, we studied silica polymorphism in these objects using an in situ micro-Raman technique. Bulk chondrule compositions define mixing lines between the compositions of olivine and pyroxene. The SRCs extend these lines to an SiO2 end member. In contrast, magmatic trends grossly deviate from these mixing lines. Concentrations of CaO, Al2O3, and REE in the pyroxenes of the SRCs are low (0.01 to 1? CI) and the CI-normalized REE-patterns are virtually flat, typical of bulk chondrules, but untypical of magmatic trends. We therefore conclude that SiO2-rich objects are not of magmatic origin. They are the result of fractional condensation in the solar nebula. The silica in SRCs occurs mainly as tridymite and sometimes as cristobalite or - in very rare cases - as quartz. Some SiO2-phases yielded a yet unknown micro-Raman spectrum, which we were unable to identify. The often chondrule-like shape of SRCs as well as the presence of high-temperature SiO2-polymorphs lead to the following model for the origin of SRCs: formation of SiO2-rich precursors in the solar nebula by fractional condensation, reheating to temperatures between 1140 and >1968 K, thereby forming the SRCs, - probably during the chondrule-forming process - followed by rapid cooling. ? 2005 Elsevier Inc. All rigths reserved.
Keywords: CHONDRITE; SILICATE